Characteristics of patients requiring non-invasive ventilation in pediatric intensive care unit - Estina, Vania Catleya; Wati, Dyah Kanya; Suparyatha, Ida Bagus; Hartawan, I Nyoman Budi (DiscoverSys Inc., 2019)
Background: Non-invasive ventilation (NIV) has become an essential tool in the treatment of both acute and chronic respiratory failure in children. This study aimed to determine the efficacy of NIV usage in pediatric patients who were admitted to the Pediatric Intensive Care Unit (PICU) with respiratory failure.Patients and Methods: This study is a retrospective, cross-sectional review. The data were collected from the medical record of PICU patients at our hospital from 2017 to 2018. Successful NIV was defined as patients who survived without intubation. Failure was defined as worsened patients and needed intubation for the rescue.Results: The total subjects of this study was 78 patients. The most common indication for NIV was ARDS (78.1%), and CPAP was the most common frequently used (78.68%). The data shows that the NIV was commonly used after extubation (52.56%) than for the first-time rescue (47.44%). The success rate of NIV after extubation were 65.85% and 34.15% failed and shifted to mechanical ventilation. The duration of NIV usage was less than three days (73.77%).Conclusion: NIV is a useful tool for the treatment of respiratory failure in pediatrics. The use of post-extubation NIV may be a valuable tool to prevent reintubation.